2015
DOI: 10.1007/s10439-015-1394-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in Heart Valve Engineering: Part IV. Computational Modeling and Experimental Studies

Abstract: Abstract-In this final portion of an extensive review of heart valve engineering, we focus on the computational methods and experimental studies related to heart valves. The discussion begins with a thorough review of computational modeling and the governing equations of fluid and structural interaction. We then move onto multiscale and disease specific modeling. Finally, advanced methods related to in vitro testing of the heart valves are reviewed. This section of the review series is intended to illustrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 154 publications
(181 reference statements)
0
27
0
Order By: Relevance
“…Some were achieved through comparisons to experimental benchmark data, 82 clinical images, 21,43,59,63 , and independent computational models. 83 The U.S. Food and Drug Administration conducted an initial study to compare flow predictions from computational fluid dynamics in an idealised cardiovascular device to experimentally measured data. 82 Other benchmark studies in cardiovascular modelling can be found in.…”
Section: Validation and Verificationmentioning
confidence: 99%
“…Some were achieved through comparisons to experimental benchmark data, 82 clinical images, 21,43,59,63 , and independent computational models. 83 The U.S. Food and Drug Administration conducted an initial study to compare flow predictions from computational fluid dynamics in an idealised cardiovascular device to experimentally measured data. 82 Other benchmark studies in cardiovascular modelling can be found in.…”
Section: Validation and Verificationmentioning
confidence: 99%
“…Such complex FSI computations however require further validation and thus need to be supported by experimental data, as pointed out before. One difficulty regarding the validation of solvers dedicated to aortic valve applications is the diversity of challenges met: (1) The geometry and the flow are complex; (2) there are FSIs between the valve leaflets and the blood; (3) the Reynolds number is sufficiently high to yield turbulence transition or at least intermittency; (4) the aorta is deformable; (5) blood and valves (either native or bioprosthetic valves) are biological materials whose characterization is far from trivial …”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Such models however need to be supported by experimental data to establish the validity and reliability of the numerical results. Nonetheless, as pointed out by Kheradvar et al, 30 there are still very few experimental validations of FSI valve models regarding flexible native or prosthetic aortic valves. Two main limitations are highlighted by Kheradvar et al 30 : the ability of FSI valve models to perform multiple cardiac cycles, probably due to the high computational cost of such FSI computations, and the difficulty to simulate the contact between the thin deformable leaflets when the valve is fully closed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet isolating the effect of each factor to study the valvular response is not feasible either in vitro or in vivo animal studies. On the other hand, computational simulations of heart valve behavior have proven to be promising tools to enhance our understanding of the valvular mechanisms and response to pathological alterations . However, existing computational models have yet to account for all the underlying features that impact the MV behavior.…”
Section: Introductionmentioning
confidence: 99%